Zinc finger protein rotund deficiency affects development of the thoracic leg in Bombyx mori. (25th May 2016) - Zhou, Chun‐Yan; Zha, Xing‐Fu; Liu, Hua‐Wei; Xia, Qing‐You
Abstract: The insect limb develops from the imaginal disc or larval leg during metamorphosis. The molecular mechanisms involved in the development from the larval to the adult leg are poorly understood. Herein, we cloned the full length of a zinc finger gene rotund from Bombyx mori ( Bmrn ), which contained a 1419 bp open reading frame, and encoded a 473 amino acid protein. Reverse transcription polymerase chain reaction and Western blot analyses demonstrated that Bmrn was expressed at higher levels in the epidermis than in other tissues tested, and it showed a very high expression level during metamorphosis. Knock‐down of Bmrn produced defects in the tarsus and pretarsus, including the fusion and reduction of tarsomeres, and the developmental arrest of pretarsus. Our data showed that Bmrn is involved in the formation of the tarsus and pretarsus, whereas its homologous gene in Drosophila has been shown to affect three tarsal segments (t2–t4), suggesting that the remodeling of the leg has involved changes in the patterning of gene regulation during evolution.